Aspirin Ameliorates Pancreatic Inflammation and Fibrosis by Inhibiting COX-2 Expression in Experimental Chronic Pancreatitis - Xu XF; Fan JW; Xin JQ; Wu N; Gao H; Duan LF; Zou WB; Zhang H; Li ZS (Dove Medical Press, 2022)
Xiao-Fan Xu,1- 3 Jian-Wei Fan,2 Jia-Qi Xin,4 Nan Wu,4 He Gao,2 Li-Fang Duan,2 Wen-Bin Zou,3 Hong Zhang,2,5 Zhao-Shen Li3 1School of Clinical Medicine, Ningxia Medical University, Yinchuan, 750004, People's Republic of China; 2Basic Medical Academy, Shaanxi University of Chinese Medicine, Xianyang, People's Republic of China; 3Department of Gastroenterology, Changhai Hospital, Shanghai, People's Republic of China; 4Department of Gastroenterology, Internal Medicine II, Klinikum Rechts der Isar, Technical University of Munich (TUM), Munich, Germany; 5Shaanxi International Cooperation Base, Shaanxi University of Chinese Medicine, Xianyang, People's Republic of ChinaCorrespondence: Zhao-Shen Li; Hong Zhang, Email zhaoshenli@smmu.edu.cn; zhangh1227@sntcm.edu.cnAim: Chronic pancreatitis (CP) is a complex and intractable disease mainly manifested as chronic inflammation and fibrosis. Aspirin(acetylsalicylic acid, ASA) has been reported to be used in the treatment of acute pancreatitis (AP), but its effectiveness on CP is unclear. This study aimed to investigate the therapeutic effects of ASA in CP mice.Methods: A murine model of CP was induced by intraperitoneal injection with 20% L-arginine. After one week of L-arginine administration, mice in the ASA treatment group were administered aspirin (100mg/kg/d) by intragastric gavage. At two, four, and six weeks after the first injection of L-arginine, mice were euthanized and the pancreas was collected for histological and molecular analysis. A second model of CP (caeruelin-induced) was used as a validation experiment to test the effect of ASA.Results: L-arginine-induced CP resulted in over-expression of the inflammatory enzyme cyclooxygenase (COX)-2. COX-2 expression decreased after ASA treatment. Pancreatic-injury inflammatory response (measured by changes in amylase, CK-19, F4/80, CD3, MCP-1, IL-6) and fibrosis degree (measured by expression of COL1A1, MMP-1 and TIMP-1) was reduce in ASA -treated mice model. The therapeutic effect of ASA was also observed in caeruelin-induced CP.Conclusion: ASA has an ameliorating effect in murine models of CP through inhibition of pancreatic inflammation and fibrosis, which may be a promising option for clinical treatment.Keywords: chronic pancreatitis, fibrosis, inflammation, aspirin, COX-2